Al-Qurû’ fi Al-Qur’an ‘Inda Al-Anbary fi Al-Adhdâd - Raushani Azza (Studia Quranika, 2018)
This study examines about the term al-Qurû in the Qur’an. Al-Qurû is one of the most popular discussions among muslim scholars and mufasir, both in terms of language and fiqh. However, there is a bate among muslim scholar and mufasir about the meaning of al-Qurû. It’s because al-Qurû is one of the sentence of al-Adhdâd wich has two meaning, especially in the Qur’an, namely haid (menstruation) and thahr. One of the most popular muslim scholar who concern in Qur’an and Arabic is al-Anbari with his book al-Adhdâd. Al-Anbari explains that Qurû has two meanings, First, al-Qurû in etymology is the formal Jama’ from aqra and qurû. Second, al-Qurû has a meaning of menstruation, thahr, or the period of iddah as a sign of being allowed to remarry after certain period of time